ПОЛОНИЗМЫ И ПОЛЬСКИЕ РЕАЛИИ В ПОВЕСТИ А. БЕСТУЖЕВА-МАРЛИНСКОГО НАЕЗДЫ - АНАНЬЕВА, НАТАЛИЯ (Slavia Occidentalis, 2020)
The article analyses Polish linguistic elements noted in Arrivals, a novel by A. Bestuzhev-Marlinsky, which describes the events on the border of Russia and Poland which occurred shortly after 1613. Words of Polish origin are presented in all the parts of speech; they are tasked with conveying the local Polish atmosphere and the characteristic speech of Poles as well as people of non-Polish origin (Jews, Russians) who came into contact with Poles.